Три короны: романы - Холт Виктория (Любовный исторический роман, 1995)
Экземпляры: ф.9 (20170417) / Инвентарный номер: 53254 / Цена: 50.00 / Сис.шифр: 84(7Сое) / Авт.знак: Х 73 / ББК: 84(7Сое=432.1)-44